Aligned Fe3O4 magnetic nanoparticle films by magneto-electrospray method. Issue 64 (16th August 2017) - Kartikowati, Christina W.; Li, Qing; Horie, Shinji; Ogi, Takashi; Iwaki, Toru; Okuyama, Kikuo
Abstract : Application of magnetic field during film deposition by electrospray enhances the magnetic performances of the film. This enhancement increased as the diameter of the constituent nanoparticles increased. Abstract : This work reports for the first time the preparation and evaluation of aligned Fe3 O4 nanoparticle films via a magneto-electrospray method, i.e., electrospray under a magnetic field. The magnetic field was applied to align the magnetic moment of Fe3 O4 particles. Well-dispersed Fe3 O4 nanoparticles (NPs) with average sizes of 10, 25, and 45 nm were obtained using a bead-mill dispersion. The Fe3 O4 nanoparticle slurries were mixed with a polyvinyl alcohol (PVA) solution and then deposited on Si-wafers under a 0.1 T magnetic field. The Fe3 O4 crystalline structures were maintained after both dispersion and deposition, as characterized by X-ray diffraction patterns. Hysteresis curves revealed that the magnetic coercivity ( H c ) of the well-dispersed nanoparticle slurries decreased owing to magnetic interactions among particles. However, the H c values of the films were larger than those of the nanoparticle slurries. The values further increased from the application of a magnetic field during film deposition. This enhancement was attributed to alignment of the magnetic moments of the Fe3 O4 NPs. These results show that tuning of the magnetic properties of materials, such as Fe3 O4 NPs, can be achieved by controlling the alignment of their magnetic moment.